Peningkatan Pemahaman Konsep Gaya melalui Metode Eksperimen pada Siswa Kelas IV SD GMIT Ende 04 - Alexia Ayu Guru; Eflinsia M. Donatus; Angelina Nata; Selfiana Theresia; Nining Sariyyah (Journal on Education, 2023)
This study aims to improve the understanding of the concept of style in grade IV students of SD GMIT Ende 04. This type of research is classroom action research. The subjects in this study were grade IV students of SD GMIT Ende 04 totaling 26 students. The procedure in this study consists of four stages that are carried out cyclically, namely the planning stage, the action stage, the observation stage and the reflection stage. The data were taken by observation techniques and field notes. This data is analyzed interactively through the stages of data reduction, data presentation, and verification. The prenelitian results show that there has been an increase in understanding of the concept of style in grade IV students of SD GMIT Ende 04 after applying the experimental method.